Some (d,α) reactions on Be9, F19, and Al27 at 27.5 MeV - Mayo, Santos; Testoni, J. E.; Bilaniuk, Oleya Miron (American Physical Society, 1964)
Fil: Mayo, Santos Comisión Nacional de Energía Atómica; Argentina